Geochemical cycling in aquifers contributes to the transport, storage and transfer of anthropogenically-derived phosphorus to surface waters - Mouchos, Evangelos M.; Johnes, Penny J.; Buss, Heather L.; Bingham, Sam T.; Matthews, Dianne; Bagnall, John P.; Gooddy, Daren C. (Frontiers in Environmental Science, 2022)
Phosphorus (P) is a key element which can contribute to the eutrophication of waters draining intensively farmed or populated catchments, driving adverse impacts on ecosystem and human health. An often overlooked source of P in permeable catchments is weathering of P-bearing minerals in bedrock. P release from primary minerals, present when the rock formed, controls background P concentrations in groundwater, but secondary P-bearing minerals may form in aquifers in the presence of anthropogenic P fluxes from agriculture and septic tanks. Using cores from the Upper Greensand (UGS) aquifer, UK, we show the relative contributions of P from primary and secondary minerals. Bulk rock chemical analysis indicates solid P concentrations of 0-0.8 wt.%, while porewater analyses from the same samples indicate phosphate-P concentrations of <5 μg/l - 1 mg/l and dissolved organic P concentrations of <5 μg/l - 0.7 mg/l. These data, coupled with core stratigraphy, reveal the presence of multiple primary and secondary P-bearing minerals in the UGS, and suggest that secondary P-bearing minerals are largely of anthropogenic origin. The weathering of primary P nodules produces a very low background P flux to surface waters, while the anthropogenic P-bearing minerals undergo rapid dissolution, re-precipitation and re-dissolution cycles, controlled by porewater pH and P concentrations, in turn controlling dissolved P flux to groundwater. We show that secondary P-bearing minerals are a dynamic component of the P transfer system linking anthropogenic activities on the land surface to P in groundwater and surface waters and contributing to the eutrophication of surface waters.